2007
DOI: 10.1152/ajpendo.00340.2006
|View full text |Cite
|
Sign up to set email alerts
|

Bezafibrate regulates the expression and enzyme activity of 11β-hydroxysteroid dehydrogenase type 1 in murine adipose tissue and 3T3-L1 adipocytes

Abstract: regulates the expression and enzyme activity of 11␤-hydroxysteroid dehydrogenase type 1 in murine adipose tissue and 3T3-L1 adipocytes. Am J Physiol Endocrinol Metab 292: E1213-E1222, 2007. First published December 26, 2006; doi:10.1152/ajpendo.00340.2006.-A clinically employed antihyperlipidemic drug, bezafibrate, has been characterized as a PPAR(␣, -␥, and -␦) pan-agonist in vitro. Recent extended trials have highlighted its antidiabetic properties in humans. However, the underlying molecular mechanism is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 53 publications
(41 reference statements)
3
22
0
Order By: Relevance
“…The exact function of PPARalpha in WAT has not received much attention because its expression level is lower compared with liver and muscle tissues. Nevertheless, our current data and the results of previous studies have identified the expression of PPAR-alpha in WAT and 3T3-L1 adipocytes [27]. The role of WAT PPAR-alpha in fatty acid oxi-mice by the changes of UCP2 and UCP3.…”
Section: Discussionsupporting
confidence: 38%
“…The exact function of PPARalpha in WAT has not received much attention because its expression level is lower compared with liver and muscle tissues. Nevertheless, our current data and the results of previous studies have identified the expression of PPAR-alpha in WAT and 3T3-L1 adipocytes [27]. The role of WAT PPAR-alpha in fatty acid oxi-mice by the changes of UCP2 and UCP3.…”
Section: Discussionsupporting
confidence: 38%
“…However, it was not clear whether the therapeutic benefit was related to benzafibrate or to a 1000 kilocalorie/day diet and a 600 kilocalorie/day exercise regimen. In addition to being a PPARα ligand, benzofibrate activates PPARγ and improves insulin sensitivity in animal models [46,47] , an effect not seen with fenofibrate [50] . Another study demonstrated that 42% of 62 patients with NAFLD had biochemical and ultrasound improvement on fenofibrate, but histologic data were not collected [51] .…”
Section: Pparα As a Target For The Treatment Of Nafldmentioning
confidence: 99%
“…Factors influencing 11β-HSD-1 expression include GCs, insulin, thyroid hormones, sex steroids, GH, IGF-1, cytokines and differentiation, determination and transcription factors such as PPARg2, C/EBPα, SREBP1c/ADD1, SPARC, NFkappaB, Stat5, or FOXO binding sites. PPARg agonists have indeed been found to modify the expression and the activity of 11β-HSD-1 in adipose tissue (Nakano et al, 2007;Kolak et al, 2007).…”
Section: Discussionmentioning
confidence: 96%